RESEARCH MODELLING IN CIVIL ENGINEERING MASTER’S THESES - Chulkov, Vitaliy (Revista Inclusiones, 2020)
There are five consecutive stages identified in the Civil Engineering learning process (Vocational school or College programme, Bachelor’s or Specialist’s programme, Master’s programme, Junior Doctorate or Junior Doctorate Military programme, Higher Doctorate programme). Each stage is completed with a qualifying parer that students or degree seekers must defended at public examinations. For the first two stages it is a diploma, and for the rest – a thesis. A transition to a subsequent educational stage envisages a higher level of theoretical development of the problem under study, independence in choosing research topic, justification of means and methods for solving research problems, and personal responsibility for the quality of the research results. Bachelor’s programme is understood as an abridged version of traditionally existed Specialist’s programme, and Master’s programme is completely innovative for Russia. The ways of eliminating the educational lacuna of Master’s programme in the Russian Federation have not yet been fully studied, the methodological approaches to the teaching technologies and to the form of completion of Master’s programme remain controversial. Directive documents of the Ministry of Education name in parallel the student’s final paper both "Master’s thesis" (by analogy with foreign traditions) and "Graduation qualification work" (by analogy with the traditional practice of the national educational process).